'Not only increase but embellish the collection': Political Satire and Lady Hervey's Imaginary Pictures. (June 2015) - Weichel, Eric
Abstract : Satirical literary portraits and caricatures were a much-loved feature of eighteenth-century cultural life. Women at the early Georgian court created circulating letters and journals that built on the literary games of French salonnières to discuss politics, sexuality, and visual art. One particularly evocative example of this little-known genre is found in a 1729 letter from Lady Hervey to Henrietta Howard, recognised mistress of George II. The letter contains a list of twenty-eight names, each juxtaposed with the name of an imaginary painting. In this article, the first two entries in the list are discussed as political texts, and their social meaning is explored through reference to specific works of art that may have informed their iconographic potential.